Substitution (Al-ibda:l) in Colloquial Arabic Dialect in Central Sudan - Ahmed, Mahgoub Dafalla (Advances in Social Sciences Research Journal, 2018)
Like most Arab countries, the contemporary linguistic situation of Arabic language in central Sudan is of two forms. Formal one, common among all Arabs, used for teaching, learning, culture, art, thought and literature (Standard Arabic, Classic Arabic or fusX\a); and informal one, which differs from one region to another, used for spontaneous understanding, spontaneous discourse and the pursuit of daily interests (Colloquial Arabic or ?`a:mmiyya). Various aims can be achieved and many aspects can be revealed through studying and comparing between the classical Arabic and Sudanese colloquial Arabic in central Sudan. One of them is identity: colloquial Arabic words uncover the original Sudanese features and express the Sudanese personality. Another aim, it helps linking the present with the past heritage. Also, it encourages emergence between nations and helps the people of this part of the country to merge with people from other parts of the Arab world and not to become isolated by their own language. Therefore, the gap between the two forms of languages can be filled. The present study explains substitution (al-ibda:l), which is an important factor in the differences among dialects. It deals with different levels of grammar for the classic and colloquial word: word, phonetic and lexicon. The study attempts to analyze the models and structures of the words and compare them with their equivalent classical words in terms of their formations and structures. This helps to establish good understanding of classical Arabic, because it is in fact parallel to the colloquial. Specially, standard Arabic is the language of the most sacred book for Muslims (Quran). The method follows theoretical interpretation of this linguistic phenomenon of the word in a comparative scientific analysis, whose task is to uncover the relationships between the linguistic structures and the establishment of these rules in the form of clear methodological laws.